Evaluating Generative Al's Effects on Human Resource Management in Light of Developing Nations (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Artificial intelligence (AI) is rapidly advancing and being applied across many domains, including human resource management (HRM), are rapidly advancing and applying artificial intelligence (AI). Generative AI that can produce human-like content has the potential to transform HRM practices,especially in developing nations with talent shortages. This paper evaluates the potential effects, risks, and benefits of using generative AI in HRM in the context of developing nations. A mixed methods approach combines literature review and case studies to assess impacts on recruitment, talent development, retention, and other HRM functions.Findings suggest generative AI could improve access to talent and skills development while requiring adjustments to evaluate AI-generated content. Risks around data bias and security would need mitigation. HRM professionals are cautiously optimistic about AI's potential but emphasize the importance of human oversight. Developing nations could benefit from AI in HRM but should proactively develop policies to govern ethical AI use. Further research is needed to develop best practices as adoption accelerates.